Iron Deficiency Anaemia in Pregnant Females and Correlation of Red Cell Indices with Serum Ferritin: A Descriptive Approach - Gandhi , Shivani; Sharma, Mahima; Sharma, Anuja; Khajuria, Arvind (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Anaemia in pregnancy is defined when haemoglobin concentration in peripheral blood is 11g/dl or less. In developing countries, the prevalence of anaemia in pregnant females is 51%. Maternal iron deficiency during pregnancy is associated with inadequate weight gain, anaemia, retarded foetal growth, low birth weights, still births, preterm delivery, intra uterine growth retardation, morbidity and mortality rates. As majority of the cases of anaemia is seen in individuals of low socio economic status, therefore in view of increased prevalence of anaemia in our country, there is a need to find an alternative cost effective method/parameter for early diagnosis of IDA. RDW is a more reliable indicator than any other red cell indices for iron deficiency especially in pregnancy.